Changes in the expression of peanut agglutinin (PNA) receptors on thymocytes in the normal condition and after prenatal administration of dexamethasone in rats - Aravitskiy, E. O.; Аравіцький, Євген Олегович (My University, 2025)
Aim: To study the dynamics of peanut agglutinin lectin (PNA) receptor expression on thymocytes in normal conditions and after prenatal administration of dexamethasone in rats.